CYP2S1 might regulate proliferation and immune response of keratinocyte in psoriasis - Yujun Sheng; Leilei Wen; Xiaodong Zheng; Mengqing Li; Dan Wang; Sixian Chen; Ran Li; Lili Tang; Fusheng Zhou (Epigenetics, 2021)
Psoriasis is an autoimmune skin disorder influenced by genetic, epigenetic and environmental factors. We previously found CYP2S1 intragenic DNA methylation cg19430423 site strongly hypomethylated in psoriatic skin tissues. In this study, we performed methylation loci fine-mapping to search the top signals in the entire CYP2S1 gene region, and further carried out gene expression assay, cell proliferation, apoptosis, differentiation and migration in CYP2S1 overexpressed (CYP2S1over) and silenced (siRNA) human keratinocytes. Target bisulphite conversion sequencing revealed cg19430423 and nearby two loci were the top differentially methylated loci. These three loci located within active enhancer region marked by H3K4Me1 and H3K27AC peaks. Cg19430423 might not bind with ATF1 directly. CYP2S1over repressed NHEK cell proliferation, but have no confirmed evidence on affecting migration, apoptosis and differentiation. Real-time PCR showed that CYP2S1 inhibited expression of IL1β, IL8, IL33, IL36, LL37, CXCL10 and CCL20 gene. In summary, CYP2S1 might inhibit keratinocyte proliferation, and modulate immune response through IL-8, IL-33, IL-36, CXCL-10, CCL20, thus contribute to the development of psoriasis.